A INFLUÊNCIA DOS FATORES CRÍTICOS DE SUCESSO NA GESTÃO POR PROCESSOS DE NEGÓCIO BPM - Paixão, Tatiane Ribeiro (2014)
This research aims to identify the critical factors that influence the success of management initiatives by business processes in order to minimize the recurring errors and contribute to a better planning of actions required to maximize the chances of success, since there are numerous variables involved in this type of approach. For this, we carried out a systematic and structured review of the literature using databases more comprehensive scientific research to describe the state of the art on the topic in question, with the identification of 52 Critical Success Factors (CSF) articles. Having regard to the FCS addressed in the literature, it was necessary to raise the critical factors that influence the success of management initiatives by business processes in the perception of a limited and select group of 17 experts in Business Process Management with the goal of developing a survey instrument (questionnaire) based both in theory and in practice. The questionnaire with 16 selected FCS was applied to 136 Brazilian Specialists in Business Process Management (BPM) with Certified Business Process Professional (CBPP), in order to map the perceptions of these professionals about the level of influence of the critical factors in the success of initiatives/projects for process management. Using descriptive statistics identified a set of 10 CSF that influence the successful practice BPM. The result of this study showed relevance to the development of knowledge to the academic community, but also for practical applications market as support for the action planning and effective management of the critical factors that influence the success of BPM initiatives tool.